2006
DOI: 10.1002/cjoc.200690247
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical Studies of Some Schiff Bases in 1,4‐Dioxane and Dimethylformamide at 318.15 K

Abstract: From experimental data of density, viscosity and ultrasonic velocity, the various acoustical properties, such as specific impedance (Z), isentropic compressibility (κ s ), Rao's molar sound function (R m ), the van der Waals constant (b), molar compressibility (W), intermolecular free length (L f ), relaxation strength (r), internal pressure (π), free volume (V f ), solvation number (S n ) etc., were calculated for three Schiff bases in 1,4-dioxane and dimethylformamide (DMF) at 318.15 K. The results are inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, little work has been done for some organic compound solutions [18][19][20][21] especially Schiff bases [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, little work has been done for some organic compound solutions [18][19][20][21] especially Schiff bases [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found most suitable to investigate various organic compounds (liquids) and Schiff bases [13]. Ultrasonic studies in aqueous and non aqueous electrolytic solutions have lead to new insight into ion-solvent interactions and provide valuable information about the ionic interactions and the nature and the strength of interactions [14].Recently many investigators have reported the influence of solvent, concentration, temperature and the nature of the substituents on the structure of Schiff bases and molecular interactions in the solutions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found most suitable to investigate various organic compounds (liquids) and Schiff bases [13]. Ultrasonic studies in aqueous and non aqueous electrolytic solutions have lead to new insight into ion-solvent interactions and provide valuable information about the ionic interactions and the nature and the strength of interactions [14].Recently many investigators have reported the influence of solvent, concentration, temperature and the nature of the substituents on the structure of Schiff bases and molecular interactions in the solutions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%